Children hospitalised with bronchiolitis in the first year of life have a lower quality of life nine months later. (2nd October 2014) - Rolfsjord, Leif Bjarte; Skjerven, Håvard Ove; Bakkeheim, Egil; Carlsen, Kai‐Håkon; Hunderi, Jon Olav Gjengstø; Kvenshagen, Bente Krane; Mowinckel, Petter; Lødrup Carlsen, Karin C.
Abstract Aim Acute bronchiolitis increases the risk of asthma, and reduced quality of life (QoL) is reported in children with asthma and allergy. However, the impact of asthma risk factors on QoL is unclear. This study investigated whether bronchiolitis and common asthma risk factors in infancy had an influence on later QoL. Methods The parents of 209 infants recruited during hospitalisation for bronchiolitis at a mean age of 4 months, and 206 controls responded to the generic Infant Toddler Quality of Life Questionnaire 9 months later. We used robust regression analyses to assess the association between four asthma risk factors, atopic eczema, parental asthma, parental allergic rhinoconjunctivitis and second‐hand smoke and QoL in the two groups. Results QoL was lower among children with previous bronchiolitis in the overall health and general health domains and lower in six of 13 domains in children with atopic eczema. Compared with no risk factors, children with previous bronchiolitis and three risk factors had lower scores in four domains, and control children with three risk factors had lower scores in three domains. Conclusion Having acute bronchiolitis, atopic eczema and three asthma risk factors were negatively associated with later QoL in early childhood.